Ø§ÙØ±Ø§ÙÙ Ø§ÙØ¹ÙÙ ÙÙ ÙØªØ§Ø¨ Ø¨ÙØ§ØºØ§Øª Ø§ÙÙØ³Ø§Ø¡ ÙØ§Ø¨Ù Ø·ÙÙÙØ± - ÙØµÙØ Ø³Ø¹ÙØ¯ Ø§ÙØ³Ø±ÙØÙ Ø§ÙØØ±Ø¨Ù, ØµÙÙØ ÙØµÙØ Ø³Ø¹ÙØ¯ Ø§ÙØ³Ø±ÙØÙ (Revues facultÃ© des lettres et des langues, 2016)
ÙØ¹Ø¯ Ø§ÙØ±Ø§ÙÙ Ø¹ØªØ¨Ø© ÙÙ Ø¹ØªØ¨Ø§Øª Ø§ÙÙØµØ ÙØ¹ÙØµØ±Ø§Ù ÙØ§ÙØ§Ù ÙÙ Ø¹ÙØ§ØµØ± Ø§ÙØ¨ÙØ§Ø¡ Ø§ÙØ³Ø±Ø¯ÙØ ÙÙÙ Ø§ÙØµØ§ÙØ¹ ÙÙØ ÙØ§ÙÙØªØÙÙ ÙÙ Ø¨ÙØ§Ø¡ Ø§ÙØ¹ÙØ§ÙØ§Øª Ø¨ÙÙ ÙÙÙÙØ§ØªÙ ÙØ§ÙÙØ³ÙØ· Ø¨ÙÙ Ø§ÙÙØ§Ø¯Ø© Ø§ÙÙØ±ÙÙØ© ÙØ§ÙÙØªÙÙÙ. ÙØ«ÙØ± Ø¨ØªØµØ¯Ø±Ù Ø§ÙÙØµ Ø§ÙØ³Ø±Ø¯Ù Ø§ÙØ¹Ø¯ÙØ¯ ÙÙ Ø§ÙØªØ³Ø§Ø¤ÙØ§Øª ØÙÙ: Ø§ÙØ¹ÙÙ Ø§ÙØªÙ Ø±Ø£Øª Ø§ÙÙØ´ÙØ¯ Ø§ÙØ³Ø±Ø¯Ù. Ø§ÙØµÙØª Ø§ÙØ°Ù ÙÙÙ ÙØ°Ù Ø§ÙØ±Ø¤ÙØ©. Ø§ÙØ²ÙÙ Ø§ÙØ°Ù ØªÙØª ÙÙÙ Ø§ÙØ±Ø¤ÙØ©. Ø¯ÙØ± Ø§ÙØ±Ø§ÙÙ ÙÙ Ø§ÙØ¨ÙØ§Ø¡ Ø§ÙØ³Ø±Ø¯Ù. ÙØªØ¨Ø¹Ø§Ù ÙÙØ°Ù Ø§ÙØªØ³Ø§Ø¤ÙØ§Øª Ø³ØªÙÙ Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø¹ÙÙ Ø§ÙØ±Ø§ÙÙ Ø¨ÙØµÙÙ Ø§ÙØ¹ÙÙ Ø§ÙØªÙ ØªØ±Ù Ø§ÙÙØ´Ø§ÙØ¯ Ø§ÙØ³Ø±Ø¯ÙØ© Ø«Ù ØªØ¹ÙØ¯ ØµÙØ§ØºØªÙØ§ ÙØªØ¬Ø¹Ù ÙÙ Ø§ÙÙØªÙÙÙ Ø´Ø±ÙÙØ§Ù ÙÙ Ø§ÙØ±ÙØ§ÙØ©. ØªØªØ®Ø° Ø§ÙØ¯Ø±Ø§Ø³Ø© ÙÙ ÙØªØ§Ø¨ Ø¨ÙØ§ØºØ§Øª Ø§ÙÙØ³Ø§Ø¡ ÙØ§Ø¨Ù Ø·ÙÙÙØ± ÙØ§Ø¯Ø© ÙÙØ§ ÙÙÙ Ø§ÙÙÙÙØ¬ Ø§ÙÙØµÙÙ Ø§ÙÙØ³ØªØ¹ÙÙ Ø¨Ø¢ÙÙØ© Ø§ÙØªØÙÙÙ Ø£Ø¯Ø§Ø© ÙÙÙÙÙØ¬ Ø¥ÙÙ Ø¹Ø§ÙÙ Ø§ÙØ³Ø±Ø¯ÙØ§Øª Â Narralology ÙÙØØ§ÙÙØ© Ø§ÙØ¥ÙØ§Ø¯Ø© ÙÙ Ø§ÙØ±ØµÙØ¯ Ø§ÙÙØ¸Ø±Ù ÙØ§ÙØ¥Ø¬Ø±Ø§Ø¦Ù ÙØ§ÙØ§ØµØ·ÙØ§ØÙ ÙÙØ³Ø±Ø¯ÙØ§Øª Ø§ÙØØ¯ÙØ«Ø© ÙØ¹ Ø§ÙÙÙØ§Ø¡ ÙÙÙØµ Ø¨Ø§Ø¹ØªØ¨Ø§Ø±Ù ÙÙØ§Ø±Ø³Ø© ÙØºÙÙØ© ÙØªÙÙØ²Ø©. Ø³ØªÙÙ Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø¹ÙÙ ÙÙÙÙÙ Ø§ÙØ±Ø§ÙÙ Ø§ÙØ¹ÙÙ ÙØ¹ÙØ§ÙØªÙ Ø¨Ø§ÙÙØ±ÙÙ Ø ÙØªØ±Ø¨Ø· Ø¨ÙÙ Ø§ÙØ±Ø¤ÙØ© Ø§ÙØ¨ØµØ±ÙØ© ÙØ§ÙÙØµÙ ØÙØªÙØ´Ù Ø¹Ù Ø§ÙØ¹ÙØ§ÙØ© Ø¨ÙÙ Ø§ÙÙØµÙ ÙØ§ÙØ³Ø±Ø¯ ØÙÙÙØµÙÙ Ø¥ÙÙ Ø£ÙÙØ§Ø· Ø§ÙØ±Ø§ÙÙ Ø§ÙØ¹ÙÙ ÙØªØØ¯ÙØ¯ Ø§ÙØ±Ø¤ÙØ© ÙØ·Ø±ÙÙØ© Ø§ÙØ±ÙØ§ÙØ© Ø¹ÙØ¯ ÙÙ ÙÙÙÙ ÙØ¯ÙØ±ÙÙ ÙÙ Ø§ÙØ¨ÙØ§Ø¡ Ø§ÙØ³Ø±Ø¯Ù . ØªÙØ¯Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø¥ÙÙ Ø§ÙØ¥Ø³ÙØ§Ù ÙÙ Ø¥Ø¹Ø§Ø¯Ø© ÙØ±Ø§Ø¡Ø© ØªØ±Ø§Ø«ÙØ§ Ø§ÙÙØ«Ø±Ù Ø¨ØµÙØ© Ø¹Ø§ÙØ©Ø ÙØ§ÙÙØµÙÙ Ø¨ØµÙØ© Ø®Ø§ØµØ© ÙÙØ§ ØªØ³Ø¹Ù Ø¥ÙÙ Ø§ÙÙØ´Ù Ø¹Ù Ø£ÙÙØ§Ø· Ø§ÙØ±Ø§ÙÙ Ø§ÙØ¹ÙÙ ÙÙ ÙØªØ§Ø¨ Ø¨ÙØ§ØºØ§Øª Ø§ÙÙØ³Ø§Ø¡ ÙØ§Ø¨Ù Ø·ÙÙÙØ± ÙØ¯ÙØ±Ù ÙÙ Ø§ÙØ¨ÙØ§Ø¡ Ø§ÙØ³Ø±Ø¯Ù . The narrator is one of the most significant narrative elements. The narrator constructs and directs elements in the narrative. The narrator is a mediator between the narrative and the recipient. Such a major role brings to light several questions regarding the eye-witness character that observes the scene of actual incident, the voice that transfers the description of the scene, the span of time for narration as well as the function of the narrator in the narrative structure. Â Â Â Â Â Â Â Â Â Â Â  The aim of this research is to propose answers for those above issues where the eye-witness narrator is concerned especially when the narrator firstly reformulates the incidents witnessed, and secondly involves the recipient to take part in the process of re-narration .Â  Â Â Â Â Â Â Â Â Â Â Â  Methodology in this study relies on descriptive and analytical approaches of the writing style in Ibn Tayfurâs Â  Balaghat al-Nisa. This study aims to contribute to the field ofÂ Â  NarratologyÂ  by undertaking to review the literatureÂ  and terminology in modern narratology. Â Giving due attention to the notion of writingÂ  in Ibn Tayfur constitutes the core of this paper.Â  Â Â Â Â Â Â Â Â Â Â Â  The paper will also investigate the relationship between the narrated and the narrator,Â  the visual and the descriptive, and the visual and the narrative. By doing so, the study explores the types of the eye-witness narrator and their means in illuminating the visual and their techniques along with their structures in narration. Â Â Â Â Â Â Â Â Â Â Â  This paper contendsÂ  to reread the Arabic heritage in prose, in general, and the descriptive narrative through Ibn Tayfurâs Â  Balaghat al-Nisa in particular. Key words: Narration, eye-witness narrator, rereading, reformulating, descriptive heritage. Â